ABOLISI DAN AMNESTI SEBAGAI INSTRUMEN PENGAMPUNAN NEGARA (STUDI KASUS TOM LEMBONG DAN HASTO KRISTIYANTO) - Elawati, Tuti; Suparman, Yusup (Gapenas Publisher, 2025)
Abolition and amnesty are instruments of state pardon granted by the President in his capacity as the holder of prerogative rights. In the Indonesian constitutional system, the President’s authority to grant abolition and amnesty is explicitly regulated in Article 14 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which stipulates that the President grants amnesty and abolition with due regard to the considerations of the House of Representatives. This provision indicates that the President’s prerogative authority is not absolute, but subject to a check-and-balance mechanism. This study employs a normative juridical method with a statutory approach and a conceptual approach. The findings reveal that the President’s prerogative rights in granting abolition and amnesty embody the principle of state sovereignty, limited by the Constitution and political legitimacy through the House of Representatives. The mechanism of application and granting involves a written request to the President, administrative verification by relevant ministries or institutions, and consideration by the House of Representatives before being finalized in a Presidential decree. Thus, the granting of abolition and amnesty is not solely the President’s prerogative, but also a constitutional instrument that must be exercised prudently, transparently, and oriented toward justice and national interest.